Frontal lobe position after single‐layer cadaveric dermal matrix repair of large anterior skull base defects. Issue 1 (31st March 2022) - Levine, Corinna G.; Al‐Rasheedi, Abdullah N.; Mantero, Alejandro; Al‐Bar, Mohammad; Casiano, Roy R.
Abstract: Objective: Endoscopic repair of large anterior skull base (ASB) defects has excellent results when using multilayered repairs with a nasoseptal flap. However, in extensive intranasal tumors, a nasoseptal flap may not always be available. One alternative option is a flexible single‐layer ASB repair. Initial studies indicate low cerebrospinal fluid leak rates with a single‐layer repair. However, the level of frontal lobe support, particularly the propensity for a significant inferior displacement of the frontal lobe, is not known. The goal of this study is to determine the frontal lobe position after single‐layer acellular dermal allograft repair in large ASB defects. Study Design: Retrospective cohort study. Setting: Tertiary care medical center. Subjects and Methods: This cohort study compares the frontal lobe position in adults who underwent endoscopic endonasal ASB tumor resection and single‐layer cadaveric dermal matrix repair (ASB cohort) with control subjects without intracranial abnormalities (control cohort). The ASB cohort includes subjects with an ASB defect of ≥5 cm anterior/posterior and ≥1.5 cm wide and who had imaging at least 2 months after surgery. The frontal lobe position is measured on sagittal CT/MRI using a reference line from the base of the sella to the nasion. A value of zero indicates that the inferior‐most aspect of the frontal lobe is at the level of the nasion−sellar line. A positive value indicates that the frontal lobe is inferior to the nasion−sellar line. The ASB cohort frontal lobe position is compared with the control cohort using the Mann−Whitney U test. A priori we set an absolute difference of 5 mm as a clinically significant difference. Results: The ASB cohort includes 47 subjects who are 57% male with an average age of 60 years (range: 31−89 years). The most common ASB pathology is esthesioneuroblastoma ( n = 21) and 81% of the ASB cohort had postoperative radiation. The control cohort includes 20 subjects who are 60% male, with a mean age of 45 years (range: 19−74 years). The majority of controls underwent imaging for head trauma ( n = 13). The ASB mean frontal lobe position is −0.2 mm superior to the nasion−sellar line (range: −9.2 to 10.4 mm), while the control's mean frontal lobe position is 1.1 mm inferior to the nasion−sellar line. This difference is not statistically significant ( P = 0.13) and does not reach our a priori definition of clinical significance. The frontal lobe position of ASB subjects who had radiation is closer to the nasion−sellar line as compared with those who did not undergo radiation. Conclusions: Single‐layer acellular dermal graft repair maintains frontal lobe support and position in large ASB defects. Key points: Single‐layer dermal graft anterior skull base repair did not demonstrate inferior displacement of the frontal lobes as compared to controls. Radiation had a negligible impact on the position of the frontal lobes after single‐layer dermal graft repair of large anterior skull base defects.